Synthesizing Archetypes of Social-Ecological Systems: Identifying Common Building Blocks - Klaus Eisenack; Graham Epstein; Lydia Finzel; Elke Kellner; Ben Nagel; Stefan Partelow; Matteo Roggero; Sergio Villamayor-Tomas (Environmental Policy and Governance, 2025)
A growing number of studies apply the social-ecological systems (SES) framework with its standardized set of variables to examine place-based environmental governance. Yet, due to the wide diversity of social-ecological systems, a general theory about how variables interact—and systems can be governed—lacks empirical support. Despite many case studies, knowledge cumulation is hindered by data heterogeneity, and by the difficulties with synthesizing a large number of cases into middle-range theories, possibly understood as re-occurring patterns of the larger theoretical puzzle of environmental governance. Thus, this paper aims to cumulate knowledge by identifying repeating configurations of variables across 71 models from SES framework case studies using archetype analysis. We propose a building-blocks approach to identify eight archetypes, each characterized by a triad (presence of three variables), an explanation of this triad, and a qualitative characterization with cases which exemplify them. The triads relate to, for example: shared operational agency; small households in remote, inaccessible places; property and accountability; or formal investment conditions. We show how a relatively small set of triads can be combined in various ways to represent a larger diversity of SES, and illustrate this by re-visiting several cases. We argue that identifying these recurring archetypes advances the field because it allows scholars to focus their theorizing and empirical research around a known set of triads. More broadly, the paper contributes to advancing empirically supported claims about SES and environmental governance, new uses of the SES framework, and techniques for knowledge cumulation using archetype analysis.
Keywords: 330; archetype analysis; knowledge cumulation; middle-range theories; model-centred meta-analysis; natural resources; social-ecological systems (SES) framework